2003
DOI: 10.1073/pnas.252753799
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor blockade reverses hypophagia and enhances locomotor activity of dopamine-deficient mice

Abstract: A denosine accumulates extracellularly from breakdown of ATP released from synaptic vesicles and also diffuses across cell membranes through adenosine transporters (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…4,24 Adenosine receptors are colocalized as heteromers with dopaminergic D2 receptors, inhibiting effects of dopaminergic transmission. 25,26 Numerous animal studies have found motor improvement in toxin-induced models of PD, 27 in dopamine-deficient mice, 28 and in drug-induced parkinsonism 29 with caffeine. Caffeine may also increase bioavailability and prolong the clinical effect of levodopa 30 (note that the clinical effect of caffeine may persist even after levodopa levels decline, suggesting that the D2 receptor interactions are also important).…”
Section: Caffeine and Edsmentioning
confidence: 99%
“…4,24 Adenosine receptors are colocalized as heteromers with dopaminergic D2 receptors, inhibiting effects of dopaminergic transmission. 25,26 Numerous animal studies have found motor improvement in toxin-induced models of PD, 27 in dopamine-deficient mice, 28 and in drug-induced parkinsonism 29 with caffeine. Caffeine may also increase bioavailability and prolong the clinical effect of levodopa 30 (note that the clinical effect of caffeine may persist even after levodopa levels decline, suggesting that the D2 receptor interactions are also important).…”
Section: Caffeine and Edsmentioning
confidence: 99%
“…Because DD mice are hypoactive and will not engage in some behaviors at all, we trained groups of DD mice after injection with caffeine (15 mg/kg), which restores locomotor activity independently of DA signaling (32). Caffeine-treated DD mice were injected with L-Dopa (30 mg/kg) before behavioral testing to determine whether learning had occurred but could not be expressed without DA signaling.…”
Section: Experimental Paradigmmentioning
confidence: 99%
“…The potential therapeutic efficacy of adenosine A 2A receptor antagonists is further demonstrated by studies showing that the motor impairment caused by genetic inactivation of the dopamine D 2 receptor is counteracted by administration of KW-6002 [75]. In addition, caffeine enhances locomotion in mice made dopamine deficient by inactivating the gene coding for tyrosine hydroxylase, the rate-limiting enzyme in the synthesis of catecholamines [162]. Studies performed in MPTP-treated monkeys show that the anti-parkinsonian effect of KW-6002, administered alone or together with dopaminomimetic drugs, is not accompanied by dyskinesia, even after several days of administration [110,160,161].…”
Section: Caffeine and Parkinson's Diseasementioning
confidence: 99%
“…Lack of behavioral sensitization is also observed following chronic administration of levodopa to A 2A knockout mice unilaterally lesioned with 6-OHDA [164]. In addition, coadministration of caffeine reduces the hyperlocomotor effect produced by levodopa in genetically altered, dopamine-deficient mice [162]. The idea that adenosine A 2A receptor antagonists possess antidyskinetic properties has been recently challenged by Lundblad et al [165].…”
Section: Caffeine and Parkinson's Diseasementioning
confidence: 99%